Value Chain Analysis of Free Fatty Acid of Rice Bran Oil in Bangladesh (Bangladesh Journal of Agricultural Research, 2022)
The study was conducted at Emerald oil mill and Poultry Industries Limited, Sherpur and Square Toiletries Ltd. at Shalghoria, Pabna to assess the financial analysis of the rice bran oil mill and to determine the value chains system of rice bran edible oil chemical by-products specially free fatty acid and actors involved in marketing of FFA in Bangladesh during the year 2013-2014. Tabular and statistical analyses were done. Results revealed that the rice bran edible oil was produced as the main product (7948 t/mill/year), and de-oil rice bran (39600 t/mill/year), free fatty acid (1495 t/mill/year), gum (332 t/mill/year), wax (329 t/mill/industry) and splint earth (808 t/mill/industry) products were also produced as chemical by-products in oil mill. Free fatty acids, gum and wax were used in soap factories. The oil mill purchased 49,500 tonnes of rice bran annually. Total cost of production was estimated at lakh Tk. 13969.85 and total variable cost was lakh Tk. 13032.98. Gross return of the oil mill was calculated at lakh Tk. 14838.03/year and lakh Tk. 867.10 was obtained from free fatty acids annually. The net profit lakh TK. 868.18/year/ industry was achieved from rice bran, while the FFA earned Tk. 30344 per ton as net profits. The benefit cost ratio was 1.06 in the oil mill. The higher return on investment was gained in free fatty acid. Minimum marketing cost was found in shorter chain-I (Oil mill – soap factory) and longer chain-III (Oil mill – Commission agent 1 – Commission agent 2 – Soap factory) produced maximum marketing cost in the FFA value chain system. Total marketing margin and total profit were achieved Tk. 10.50/kg and Tk. 2.90/kg, respectively. Free fatty acid as a chemical byproduct in rice bran oil processing has esteemed market value in soap factories that contribute to the national economy.Bangladesh J. Agril. Res. 45(4): 379-393, December 2020